2020
DOI: 10.4414/smw.2020.20236
|View full text |Cite
|
Sign up to set email alerts
|

Guideline of the Swiss Society of Gynaecology and Obstetrics (SSGO) on acute and recurrent urinary tract infections in women, including pregnancy

Abstract: Acute and recurrent urinary tract infections (UTIs) are common auto-infectious diseases transmitted from the intestinal tract. They affect the urinary tract either through recurrence or through persistence. The incidence of UTIs increases with age and comorbidities. In this guideline from the Swiss Society of Gynaecology and Obstetrics (SSGO), diagnosis and treatment of UTIs are grouped into uncomplicated and complicated cases. This is to our knowledge the first guideline that specifically considers UTIs in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 49 publications
0
41
0
3
Order By: Relevance
“…14 Ó 2022 The Authors. BJU International published by John Wiley & Sons Ltd on behalf of BJU International.rUTI in women, including in the context of pregnancy, and urogynaecological diagnoses and surgery[19]. rUTI management in men was not included.The Spanish Society of Infectious Diseases and Clinical Microbiology (SEIMC) published in 2017 their consensus statement paper 'Executive summary of the diagnosis and treatment of urinary tract infection: Guidelines of the Spanish Society of Clinical Microbiology and Infectious Diseases (SEIMC)'[20].The Association of Scientific Medical Societies in Germany (AWMF [Arbeitsgemeinschaft der WissenschaftlichenMedizinischen Fachgesellschaften]) S3 Guideline is written in German.…”
mentioning
confidence: 99%
“…14 Ó 2022 The Authors. BJU International published by John Wiley & Sons Ltd on behalf of BJU International.rUTI in women, including in the context of pregnancy, and urogynaecological diagnoses and surgery[19]. rUTI management in men was not included.The Spanish Society of Infectious Diseases and Clinical Microbiology (SEIMC) published in 2017 their consensus statement paper 'Executive summary of the diagnosis and treatment of urinary tract infection: Guidelines of the Spanish Society of Clinical Microbiology and Infectious Diseases (SEIMC)'[20].The Association of Scientific Medical Societies in Germany (AWMF [Arbeitsgemeinschaft der WissenschaftlichenMedizinischen Fachgesellschaften]) S3 Guideline is written in German.…”
mentioning
confidence: 99%
“…Of the 13 guidelines coming from 4 different continents ( Table 1 ), 8 came from Europe, produced on behalf of the European Association of Urology (EAU) [ 7 ], German Society of Urology (German acronym: DGU) [ 11 ], Swiss Society of Gynaecology and Obstetrics (SSGO) [ 12 ], Spanish Society of Clinical Microbiology and Infectious Diseases (SEIMC) [ 13 ], joint report of French Infectious Diseases Society/Urological French Association (French acronym: SPILF/AFU) [ 14 ], joint report of the Institute of Obstetricians and Gynaecologists, Royal College of Physicians of Ireland/Clinical Strategy and Programs Division, Health Service Executive (IOGRCPI/ CSPDHSE) [ 15 ] and 2 guidelines coming from the National Institute for Health and Care Excellence (NICE) [ 16 , 17 ]; 1 from North America, produced on behalf of the Infectious Diseases Society of America (IDSA) [ 18 ]; 3 from South America, produced on behalf of the joint report of the Brazilian Society of Infectious Diseases/Brazilian Federation of Gynecology and Obstetrics Associations/Brazilian Society of Urology/Brazilian Society of Clinical Pathology/Laboratory Medicine (SBI/FEBRASGO/SBU/SBPC/ML) [ 19 ], joint report of the Argentinean Society of Infectious Disease (SADI) [ 20 ] and Colombian Association of Infectious Disease (Spanish acronym: ACIN) [ 21 ]; and 1 from Oceania, produced on behalf of South Australian Health (SAH) [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported the drop-out rate (24%), while only one series required either an active UTI or history of UTI at study entry, although varying criteria and validated tools to define rUTIs were used. Despite the concept of ‘culture-negative’ UTI having emerged, which recognizes the demonstrated effect of antibiotics to resolve UTI symptoms in women who did not demonstrate a culture growth of uropathogens or who had low colony-count infections, it is common in clinical practice to initiate treatment without or before culture results are available, creating a significant bias [ 18 ]. In all clinical series, the medical device was adequately tolerated, resulting in excellent compliance, as negligible side effects were registered [ 19 ].…”
Section: Discussionmentioning
confidence: 99%